INFLUENCE OF RED MUD AS A CATALYST IN THE THERMO-CATALYTIC REFORMING PROCESS - Onyishi, Hillary O.; Neidel, Johannes; Daschner, Robert; Apfelbacher, Andreas; Hornung, Andreas (European Biomass Conference and Exhibition Proceedings, 2023)
Thermo-catalytic reforming (TCR®), a recently invented thermochemical process for the conversion of biomass into biofuels, combines intermediate pyrolysis and catalytic reforming to produce improved products compared to products from pyrolysis. The quality and quantity of the catalyst are vital in determining the yields and qualities of the products. Normally, the non-reactive components of the char produced in the process act as the catalyst in the process. But adding another material of good catalytic quality may affect the yields and qualities of the products. This work studies red mud (bauxite residue) as a support catalyst in the TCR® processing of woody biomass, digestate, and straw. The results, compared to the control experiments, show the introduction of the red mud generally reduces the biochar yield and generally increases the biogas and process water yields while the biooil yield remains fairly the same. In addition, its introduction increases the hydrogen fraction of the gas and slightly improves the quality of the biooil. Therefore, the results suggest red mud is a good support catalyst for increasing the production of green hydrogen, reducing the char yield, increasing the process water yield, and improving the quality of the biooil from the TCR®process.
CRIS-Team Scopus Importer:2024-12-16
Keywords: biofuels; biomass; hydrogen; pyrolysis; thermochemical conversion